2015
DOI: 10.1155/2015/387094
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Inflammation and Arthritis by Orally Administrated Cardiotoxin fromNaja naja atra

Abstract: Cardiotoxin (CTX) from Naja naja atra venom (NNAV) reportedly had analgesic effect in animal models but its role in inflammation and arthritis was unknown. In this study, we investigated the analgesic, anti-inflammatory, and antiarthritic actions of orally administered CTX-IV isolated from NNAV on rodent models of inflammation and adjuvant arthritis. CTX had significant anti-inflammatory effects in models of egg white induced nonspecific inflammation, filter paper induced rat granuloma formation, and capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…FCA induced AA model is a chronic, systemic, autoimmune inflammation mediated by T cells. It is very similar to human RA in histopathological and laboratory parameters and is ideal models for screening and studying drugs for treating RA ( Chen C.X et al, 2015 ; Qian et al, 2017 ). AA rats mainly manifested as multiple peripheral arthritis and local joint swelling, deformity, pathological changes of proliferative synovitis, articular cartilage damage, bone erosion, inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…FCA induced AA model is a chronic, systemic, autoimmune inflammation mediated by T cells. It is very similar to human RA in histopathological and laboratory parameters and is ideal models for screening and studying drugs for treating RA ( Chen C.X et al, 2015 ; Qian et al, 2017 ). AA rats mainly manifested as multiple peripheral arthritis and local joint swelling, deformity, pathological changes of proliferative synovitis, articular cartilage damage, bone erosion, inflammatory cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zhu et al demonstrated that cobrotoxin, a short-chain neurotoxin form NNAV, ameliorated body inflammatory reactions on three rodent experimental inflammation models: formaldehyde-induced mouse foot swelling test, mouse abdominal capillary osmosis test, and Whatman paper-inducing rat granuloma formation test [ 54 ]. Cardiotoxin from NNAV also presented anti-inflammatory actions on formalin test, egg-white-induced non-specific inflammation test, formalin-soaked filter papers triggered granuloma test, and abdominal capillary osmosis test [ 55 ]. These studies illustrated that cobra venom and neurotoxins possessed anti-inflammatory capabilities.…”
Section: Effect Of Nnav and Its Components On Inflammation And Immmentioning
confidence: 99%
“…In the research of NNAV, Zhu [ 11 ] proved that NNAV ameliorated paw edema and pathological lesions in adjuvant arthritis rats, and NNAV also reduced serum TNF-α levels and elevated serum interleukin-10 (IL-10) concentrations, indicating that NNAV may relieve adjuvant arthritis via attenuating inflammation. Furthermore, Chen [ 55 ] demonstrated that cardiotoxin from NNAV administrated to rats obtained a significantly lower mean arthritic score versus model adjuvant arthritis rats in pathological sections. Meanwhile, cardiotoxin decreased serum pro-inflammatory cytokines interleukin-6 (IL-6) and IL-17 expressions, while selectively inhibiting CD4 + T subsets on peripheral blood cells in adjuvant arthritis rats.…”
Section: Research Of Nnav and Its Components On Inflammatory And Imentioning
confidence: 99%
“…Previous research also indicates that LPS could induce the formation of multinucleated cells with expressed TRAP protein via the nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinases (MAPKs) pathways [ 24 ]. On the other hand, adjuvant-induced arthritis (AIA) and type II collagen-induced arthritis (CIA) are also widely used animal models for the study of RA, and for evaluating the therapeutic potential of anti-RA agents [ 25 , 26 , 27 ]. High levels of pro-inflammatory cytokines and TRAP-positive multinucleated cells that drive RA progression have also been detected in animal models [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%